Genomic Diversity of Pigeon Pea (Cajanus cajan L. Millsp.) Endosymbionts in India and Selection of Potential Strains for Use as Agricultural Inoculants - Jorrin, Beatriz; Maluk, Marta; Atoliya, Nagvanti; Kumar, Shiv Charan; Chalasani, Danteswari; Tkacz, Andrzej; Singh, Prachi; Basu, Anirban; Pullabhotla, Sarma VSRN; Kumar, Murugan; Mohanty, Santosh Ranjan; East, Alison K.; et al. (Frontiers in Plant Science, 2021)
Pigeon pea (Cajanus cajan L. Millsp. ) is a legume crop resilient to climate change due to its tolerance to drought. It is grown by millions of resource-poor farmers in semiarid and tropical subregions of Asia and Africa and is a major contributor to their nutritional food security. Pigeon pea is the sixth most important legume in the world, with India contributing more than 70% of the total production and harbouring a wide variety of cultivars. Nevertheless, the low yield of pigeon pea grown under dry land conditions and its yield instability need to be improved. This may be done by enhancing crop nodulation and, hence, biological nitrogen fixation (BNF) by supplying effective symbiotic rhizobia through the application of “elite” inoculants. Therefore, the main aim in this study was the isolation and genomic analysis of effective rhizobial strains potentially adapted to drought conditions. Accordingly, pigeon pea endosymbionts were isolated from different soil types in Southern, Central, and Northern India. After functional characterisation of the isolated strains in terms of their ability to nodulate and promote the growth of pigeon pea, 19 were selected for full genome sequencing, along with eight commercial inoculant strains obtained from the ICRISAT culture collection. The phylogenomic analysis [Average nucleotide identity MUMmer (ANIm)] revealed that the pigeon pea endosymbionts were members of the genera Bradyrhizobium and Ensifer. Based on nodC phylogeny and nod cluster synteny, Bradyrhizobium yuanmingense was revealed as the most common endosymbiont, harbouring nod genes similar to those of Bradyrhizobium cajani and Bradyrhizobium zhanjiangense. This symbiont type (e.g., strain BRP05 from Madhya Pradesh) also outperformed all other strains tested on pigeon pea, with the notable exception of an Ensifer alkalisoli strain from North India (NBAIM29). The results provide the basis for the development of pigeon pea inoculants to increase the yield of this legume through the use of effective nitrogen-fixing rhizobia, tailored for the different agroclimatic regions of India.